(untitled) (The International Journal of Educational Sciences and Arts, 2024)
Objectives: The study aimed to identify the effect of using the “Productive Struggle” strategy in improving conceptual understanding of mathematics among fifth-grade students. Methodology: The study used the quasi-experimental method with a pre-post measurement. The study sample consisted of (30) students who were distributed equally into the two groups of the control and experimental study. And to achieve the objectives of the study, a conceptual understanding test was constructed with the three demonstrations (Explanation, Interpretation, Application), and its validity and reliability were verified in addition. To the observation card to determine the level of employment of “Productive Struggle” types among fifth grade students. Results: The results of the study showed that there were statistically significant differences between the arithmetic averages of the performance of students in the experimental and control groups in the conceptual understanding test and each of its manifestations and in employing the “Productive Struggle” types due to the teaching method and in favor of the experimental group. Conclusion: In light of the results of the study, the researchers recommend the necessity of employing the “Productive Struggle” strategy in teaching mathematics to fifth-grade students.